Dialoog : tijdschrift voor homofilie en maatschappij. (Amsterdam : Dialoog, 1965)
Fonds Suzan Daniel (FSD)
Periodiciteit : tweemaandelijks
Redactie : Keizersgracht 518, Amsterdam ; vanaf (1965) 4 : PB 1564 Amsterdam
Met dubbel nummer (1965) 2 want geannoteerd
Nederlands
Periodiek